2017
DOI: 10.1186/s12936-017-1825-9
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin and malaria control

Abstract: As the world begins to realize the very real prospect of eliminating malaria as a public health problem globally, the scientific community is acutely aware that novel and innovative new tools will be required if that lofty goal is to be accomplished. Moreover, the need for comprehensive, integrated products and interventions is being recognized in order for the critical ‘final steps’ toward elimination to be taken successfully. Failure to take these crucial last steps have dogged all past global disease elimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…Moreover, ivermectin availability was greater when the drug was administered in a hydroalcoholic solution, in comparison with a solid capsule formulation or a tablet (63). With the oral dose (400 g/kg) recommended by French authorities to control lymphatic filariasis (64), ivermectin plasma concentrations could reach up to 260 ng/ml when the drug was given with food, with a time to the maximal plasma concentration Ivermectin has a large volume of distribution (3.1 to 3.5 liters/kg) due to its high lipid solubility and its extensive protein binding (unbound fraction of Ͻ0.1), and the peak plasma concentration occurs approximately 4 h after oral dosing, with a second peak at 6 to 12 h, probably arising due to enterohepatic recycling, and a plasma half-life of ϳ12 h (60,65,66). A recent study investigating the malaria-transmissionblocking potential of ivermectin used concentrations of 300 g/kg or 600 g/kg given on 3 consecutive days (total dose of 900 g/kg or 1,800 g/kg, respectively) in a fasted state, reaching plasma concentrations of around 69.4 ng/ml (range, 34.1 to 196.3 ng/ml) or 118.9 ng/ml (range, 45.2 to 455.1 ng/ml), respectively, and showed that these doses were well tolerated and reduced mosquito survival rates for at least 28 days after treatment (67,68).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ivermectin availability was greater when the drug was administered in a hydroalcoholic solution, in comparison with a solid capsule formulation or a tablet (63). With the oral dose (400 g/kg) recommended by French authorities to control lymphatic filariasis (64), ivermectin plasma concentrations could reach up to 260 ng/ml when the drug was given with food, with a time to the maximal plasma concentration Ivermectin has a large volume of distribution (3.1 to 3.5 liters/kg) due to its high lipid solubility and its extensive protein binding (unbound fraction of Ͻ0.1), and the peak plasma concentration occurs approximately 4 h after oral dosing, with a second peak at 6 to 12 h, probably arising due to enterohepatic recycling, and a plasma half-life of ϳ12 h (60,65,66). A recent study investigating the malaria-transmissionblocking potential of ivermectin used concentrations of 300 g/kg or 600 g/kg given on 3 consecutive days (total dose of 900 g/kg or 1,800 g/kg, respectively) in a fasted state, reaching plasma concentrations of around 69.4 ng/ml (range, 34.1 to 196.3 ng/ml) or 118.9 ng/ml (range, 45.2 to 455.1 ng/ml), respectively, and showed that these doses were well tolerated and reduced mosquito survival rates for at least 28 days after treatment (67,68).…”
Section: Discussionmentioning
confidence: 99%
“…The most used endectocide drug (it has activity against endo- and ectoparasites when applied to the host) in human and livestock is Ivermectin, capable of killing a wide variety of parasites and vectors [42,43]. It targets a broad range of parasites and invertebrates, including mosquitoes [44–47], and it has been proposed as an additional tool to control vector-borne diseases such as malaria [4854].…”
Section: Discussionmentioning
confidence: 99%
“…Another approach for controlling mosquitoes is based on endectocide ivermectin, a molecule that has been used for more than 30 years to control lymphatic filariasis. This molecule remains in the human bloodstream following a standard oral dose and can kill Anopheles mosquitoes that feed on the blood of medicated persons [76][77][78][79]. Controlling vector mosquito populations is a difficult task and so the addition of new technologies to be considered for IVM will help improve the effectiveness of vector-borne disease transmission [80][81][82][83].…”
Section: New Tools To Fight Malaria Vectors In An Ivm Perspectivementioning
confidence: 99%
“…The most important topics to be considered that are also in agreement with the WHO criteria, comprise: (1) assessment of the health system limitations to improve processes and methods aiming for the improvement in efficacy of vector control; (2) implementation of mosquito surveillance for the development of guidelines and models of the risk of disease transmission ( Figure 3); (3) development of effective and environmentally friendly strategies to reduce malaria and other vector-borne disease transmission, following the recommendations by VCAG and considering the increase of insecticide resistance [100,102]. To our understanding, traditional insecticide-based control efforts, such as IRS and LLIN, should be used in combination with novel eco-friendly tools, such as "eave tubes technology," ATSB methods, and even the employment of the ectendocide ivermectin [40,44,76]. These new mosquito control tools should be accompanied by (4) an evaluation of their effectiveness, assessment of their usefulness and impact through randomized controlled trials with entomological and epidemiological outcomes (Figure 3), this has been done for traditional control strategies such as LLINs and IRS; (5) the monitoring of man-made alteration in the environment and its impact in the dynamics of malaria vectors; and (6) the establishment of a multi-disciplinary team with different areas of expertise (Figure 3) [100,102,120].…”
Section: Conclusion and Issues To Watch Formentioning
confidence: 99%